Tooth Discoloration Induced by Endodontic Phenothiazine Dyes in Photodynamic Therapy - Figueiredo, Romulo Aguiar; Anami, Lilian Costa [UNESP]; Mello, Isabel; Carvalho, Erica dos Santos; Habitante, Sandra Marcia; Raldi, Denise Pontes (Mary Ann Liebert, Inc, 2014)
Objective: This study sought to assess if discoloration of tooth structures occurs after photodynamic therapy (PDT) and to determine the efficacy of a protocol to remove the photosensitizers. Background data: PDT has been used in root canal treatment to enhance cleaning and disinfection of the root canal system. PDT uses a low power laser in association with a dye as a photosensitizer. Photosensitizers can induce staining of the dental structures, resulting in an unaesthetic appearance. Methods: Forty teeth were randomly divided into four groups according to the photosensitizer used and pre-irradiation time: 0.01% methylene blue for 5 min (MB5); 0.01% methylene blue for 10 min (MB 10); 0.01% toluidine blue for 5 min (TB5); and 0.01% toluidine blue for 10 min (TB 10). Specimens were irradiated with a 660 nm diode laser with a 300 mu m diameter optical fiber, at 40 mW power setting for 3 min. Immediately after, the photosensitizers were removed with Endo-PTC cream +2.5% sodium hypochlorite (NaOCl). The shade was measured by a Vita Easyshade spectrophotometer based on the CIELAB color system (L*a*b* values) at three different experimental times: before PDT (T0), immediately after PDT (T1), and after removal of the photosensitizer (T2). Results: The results showed a decrease in the averages of the L*a*b* coordinate values after PDT (T1) in all the groups, when compared with the number at T0, with a significant statistical difference in group MB10. After photosensitizer removal (T2), all the values of the coordinates increased with significant statistical differences (p < 0.05) between T1 and T2 in L* and a*. Conclusions: It can be concluded that both methylene blue and toluidine blue dyes cause tooth discoloration, and that Endo-PTC cream associated with 2.5% NaOCl effectively remove these dyes, regardless of the pre-irradiation time used for PDT.